Targeting Tumor Physical Microenvironment for Improved Radiotherapy (Small Methods 11/2022). Issue 11 (17th November 2022) - Wang, Jin; Han, Yulong; Li, Yuan; Zhang, Fengping; Cai, Mengjiao; Zhang, Xinyue; Chen, Jie; Ji, Chao; Ma, Jinlu; Xu, Feng
Abstract : Inside Back Cover In article number 2200570, Ma, Xu, and co‐workers highlight the biophysical cue, a new hallmark of cancer, serving as a significant factor in tumor microenvironment forming a physical microenvironment, including extracellular matrix microarchitecture, stiffness, interstitial fluid pressure, and solid stress. It plays an essential role in affecting radiotherapy efficacy. Meanwhile, radiotherapy also affects tumor physical microenvironment, leading to different cancer cell behaviors. Targeting tumor physical microenvironment may greatly improve radiosensitivity.